The Major Trends in Armenia’s Foreign Policy-Making and the Macro-Regional Priorities of Russia and the United States: 2018-2020 - Aglyan, Vahagn (YSU Journal of International Affairs, 2022)
The article examines the main trends and transformations in the foreign policy of the Republic of Armenia in conjunction and in the context of the macro-regional interests of the US and the Russian Federation, the influence of structural and situational factors on some aspects of Armenia's foreign policy. In particular, the main drivers and structural circumstances that predetermined the preservation and sustainability of the long-term foreign policy of the Republic of Armenia are reflected, with a certain shift in political and discursive emphasis in relations with the two largest players in the South Caucasus. The focus is also on some problematic aspects related to changes in the general approaches of Russia and the United States in the post-Soviet space.
Keywords: RA; foreign policy; complementarism; USA; RF; South Caucasus; regional conflicts